Association between the Korean Triage and Acuity Scale level and hospitalization of children with abdominal pain in the emergency department - Sehoon Kim; Seon Hee Woo; Kyong Ho Choi; Young Min Oh; Se Min Choi; Yeon Young Kyong (Pediatric Emergency Medicine Journal, 2017)
Purpose The Korean Triage and Acuity Scale (KTAS) is a triage tool for patients in the emergency department (ED). We aimed to investigate the association between the KTAS level and hospitalization of children with abdominal pain, a common chief complaint in the ED. Methods This study retrospectively reviewed medical records of children aged 3 to 14 years who visited the ED with abdominal pain as a chief complaint. KTAS level (1-3 vs. 4-5), age, gender, presence of associated symptoms (vomiting, diarrhea, hematochezia, and fever), and disposition (rapid discharge, discharge after intravenous hydration, and hospitalization) were collected and compared between the children with KTAS 1-3 and 4-5. Results Of 1,050 children enrolled, 618 (58.9%) were classified as KTAS 1-3, and 36 (3.4%) were hospitalized. Vomiting was the most common associated symptom in both groups (63.6%), and 41.5% underwent discharge after intravenous hydration. The children with KTAS 1-3 were more frequently hospitalized (5.0% vs. 1.2%, P < 0.001). Conclusion The KTAS may be reliable to predict the hospitalization of children with abdominal pain in the ED with additional consideration of the associated symptoms.